2021
DOI: 10.1021/acs.chemrestox.0c00517
|View full text |Cite
|
Sign up to set email alerts
|

DNA Sequence Modulates the Efficiency of NEIL1-Catalyzed Excision of the Aflatoxin B1-Induced Formamidopyrimidine Guanine Adduct

Abstract: Dietary exposure to aflatoxins is a significant risk factor in the development of hepatocellular carcinomas. Following bioactivation by microsomal P450s, the reaction of aflatoxin B 1 (AFB 1 ) with guanine (Gua) in DNA leads to the formation of stable, imidazole ring-opened 8,9-dihydro-8-(2,6-diamino-4-oxo-3,4dihydropyrimid-5-yl-formamido)-9-hydroxyaflatoxin B 1 (AFB 1 -FapyGua) adducts. In contrast to most base modifications that result in destabilization of the DNA duplex, the AFB 1 -FapyGua adduct increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“… 4 , 37 , 38 In contrast, studies using human endonuclease VIII-like 1 (NEIL1) revealed that in addition to the well-known incision of the hydroxyl radical-induced 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua) and 4,6-diamino-5-formamidopyrimidine (FapyAde), 39 , 40 both unedited NEIL1 (K242) and edited NEIL1 (K242R) recognize and excise AFB 1 –FapyGua from multiple sequence contexts in oligodeoxynucleotides and genomic DNAs. 4 , 41 44 Moreover, Neil1 –/– mice treated with AFB 1 accumulated significantly greater levels of AFB 1 –FapyGua in their liver DNA and developed HCCs at frequencies higher than wild-type or NER-deficient Xpa –/– mice. 41 Among human populations, there are known polymorphic variants of NEIL1 with altered DNA glycosylase, β-elimination, and δ-elimination activities.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“… 4 , 37 , 38 In contrast, studies using human endonuclease VIII-like 1 (NEIL1) revealed that in addition to the well-known incision of the hydroxyl radical-induced 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua) and 4,6-diamino-5-formamidopyrimidine (FapyAde), 39 , 40 both unedited NEIL1 (K242) and edited NEIL1 (K242R) recognize and excise AFB 1 –FapyGua from multiple sequence contexts in oligodeoxynucleotides and genomic DNAs. 4 , 41 44 Moreover, Neil1 –/– mice treated with AFB 1 accumulated significantly greater levels of AFB 1 –FapyGua in their liver DNA and developed HCCs at frequencies higher than wild-type or NER-deficient Xpa –/– mice. 41 Among human populations, there are known polymorphic variants of NEIL1 with altered DNA glycosylase, β-elimination, and δ-elimination activities.…”
Section: Introductionmentioning
confidence: 96%
“…As with other bulky adducts, AFB 1 –N7-Gua and AFB 1 –FapyGua are substrates for the nucleotide-excision repair (NER) pathway in Escherichia coli and mammalian cells. , Although several investigations have explored a role for base excision repair of aflatoxin adducts in E. coli, the data have been inconclusive. ,, In contrast, studies using human endonuclease VIII-like 1 (NEIL1) revealed that in addition to the well-known incision of the hydroxyl radical-induced 2,6-diamino-4-hydroxy-5-formamidopyrimidine (FapyGua) and 4,6-diamino-5-formamidopyrimidine (FapyAde), , both unedited NEIL1 (K242) and edited NEIL1 (K242R) recognize and excise AFB 1 –FapyGua from multiple sequence contexts in oligodeoxy­nucleotides and genomic DNAs. , Moreover, Neil1 –/– mice treated with AFB 1 accumulated significantly greater levels of AFB 1 –FapyGua in their liver DNA and developed HCCs at frequencies higher than wild-type or NER-deficient Xpa –/– mice . Among human populations, there are known polymorphic variants of NEIL1 with altered DNA glycosylase, β-elimination, and δ-elimination activities. Data suggest that individuals carrying the variants of NEIL1 with reduced or no catalytic activity may be at an elevated risk of AFB 1 -induced HCCs.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, mechanism(s) that define sequence-dependent occurrence of AFB 1 -induced mutations likely operates prior to replication. Consistent with such possibility, we recently have demonstrated that sequence context modulates the catalytic efficiency of human glycosylase NEIL1 acting on AFB 1 -FapyGua, with rates of reactions being inversely correlated with thermal stability of the adduct-containing DNA (Tomar et al 2021). We speculate that AFB 1 -FapyGua in a more thermally-stable local environment would be more likely to escape repair not only by NEIL1, but also by nucleotide excision repair and thus, largely contribute to the final mutational signature of AFB 1 .…”
Section: Mutagenic Potential Of Afbmentioning
confidence: 57%
“…These were annealed with the corresponding 6-mer oligodeoxynucleotides (5 0 -TAGCTA-3 0 , 5 0 -TAGCGA-3 0 , 5 0 -TAGCAA-3 0 , and 5 0 -TATCGA-3 0 ) to form partially double-stranded DNA structures and reacted with AFB 1 exo-8,9-epoxide. The conditions for chemical modifications, purification by reverse-phase HPLC, and characterization by mass spectrometry were previously described (Li et al, 2015;Tomar et al, 2021) (Figure S1).…”
Section: Synthesis Of Oligodeoxynucleotides Containing Site-specific ...mentioning
confidence: 99%